Dakwah Rahmatan lil al-Alamin as Solutive Da'wah: A Study of the Study of Tafsir Science with the Approach of Sharah Hadith - M. Irfan Farraz Haecal Kusnadi (Ar-Raniry: International Journal of Islamic Studies, 2022)
The purpose of writing this article is to discuss how true Islamic da'wah is in accordance with the context of "rahmatan lil alamin", this is very important in the midst of the search for a solutive da'wah method in the midst of the massive discrediting of Muslims in the eyes of the world. This study uses a qualitative method with a measurable descriptive approach, namely research that does not actually require a direct process of collecting data but from a literature study, further this research uses the Koran published by the Ministry of Religion of the Republic of Indonesia as the premiere source, and complements it with journals, books, and other scientific proceedings as secondary sources. This study resulted in the conclusion that preaching Islam is actually not limited to just spreading religion, preaching Islam in the concept of "Rahmatan lil alamin" itself must contain the values of compassion, as Islam as a religion, in general, every religion teaches to spread love to each other.